2015
DOI: 10.1158/1940-6207.capr-15-0180
|View full text |Cite
|
Sign up to set email alerts
|

Paired Box 5 Methylation Detection by Droplet Digital PCR for Ultra-Sensitive Deep Surgical Margins Analysis of Head and Neck Squamous Cell Carcinoma

Abstract: Molecular deep surgical margin analysis has been shown to predict locoregional recurrences of head and neck squamous cell carcinoma (HNSCC). In order to improve the accuracy and versatility of the analysis, we used a highly tumor-specific methylation marker and highly sensitive detection technology to test DNA from surgical margins. Histologically cancer-negative deep surgical margin samples were prospectively collected from 82 eligible HNSCC surgeries by an imprinting procedure (n=75) and primary tissue colle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The survival difference between the two identified clusters, cluster 4 vs. cluster 6, represented a clear difference in the lifetime of these patients. These results fall in agreement with previous reports that showed a significant association between promoter methylation status and worse OSCC patients' survival [31][32][33][34]. These results demonstrated the utility of epigenetic alterations detection for potential clinical application in OSCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…The survival difference between the two identified clusters, cluster 4 vs. cluster 6, represented a clear difference in the lifetime of these patients. These results fall in agreement with previous reports that showed a significant association between promoter methylation status and worse OSCC patients' survival [31][32][33][34]. These results demonstrated the utility of epigenetic alterations detection for potential clinical application in OSCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…Dysregulated expression of PAX5 is involved in differentiation block (55), somatic hypermutation and immunoglobulin heavy chain class switch recombination (56), leukemogenesis (57), and positive regulation of c-Met transcription (58). PAX5 association to different tumor types suggests it has diagnostic or prognostic utility in lung cancer (59), Hodgkin lymphoma (60), acute lymphocytic leukemia (61), breast cancer (61), oral cancer (62,63), gastric cancer (64), head and neck cancer (65,66), and esophageal cancer (66). A recent study demonstrated that the lack of expression of PAX5 in lymphoid neoplasms is associated with promoter hypermethylation, leading to PAX5 silencing in cases characterized by poor clinical outcome (67).…”
Section: Discussionmentioning
confidence: 99%
“…The bisulfite-modified DNA was used as a template for fluorescence-based QMSP as described. 5,6,47 The primer and probe sequences are shown in Supplementary Table S2. QMSP assays were performed in triplicate using StepOnePlus (Thermo Fisher Scientific).…”
Section: Qmspmentioning
confidence: 99%